O PROCESSO DE URBANIZAÇÃO E AS POLÍTICAS URBANAS DE SALVADOR - Fonseca, Marcos de Meirelles (2011)
The consequences of urban development in the cities of Salvador that make up the Metropolitan Region (RMS) and identification of vectors of expansion by the urban policies of this Capital, is the theme that characterizes the object of study of this dissertation. Initially, the author of the work justifies the choice of theme, showing the economic importance that the city of Salvador and its RMS have on the economy of the Northeast. We then discuss the size of the Brazilian real estate market, and analyzes the urbanization as a continuous process and uneven, presenting his concept, explaining the significance of space and territory. Informs on the functioning of cities and their economies, and through a historical analysis, attempts to show the construction of urban development in Salvador, its interdependence with the Metropolitan Region and Recôncavo region, and also the origin of these cities, emphasizing its geography, economic and social, seeking also to identify options and political constraints to urban development in Salvador. This paper then aims to seek a relationship between the historical, political, religious, geographic and economic occupation of the town of Salvador, and its influence beyond its territory. Finally, he weaves the final considerations, and presents the bibliography references that founded the study for the elaboration of this dissertation.